Successful pedicled vertical rectus abdominis myocutaneous flap reconstruction with negative-pressure wound therapy for deep sternal wound infection: a case report and comprehensive review - Lee, Dong Yun; Eo, SuRak; Lim, SooA; Yoon, Jung Soo (Frontiers in Surgery, 2023)
INTRODUCTION: Deep sternal wound infection (DSWI) is a serious complication that may occur after median sternotomy, with potentially devastating consequences. By reporting our case and analyzing the existing literature, this article aimed to provide a thorough understanding of the role of negative-pressure wound therapy (NPWT) and the importance of flap choice in managing DSWI accompanied by severe heart injury and high hemodynamic risk. CASE DESCRIPTION: A 60-year-old woman with severe aortic stenosis, aortic valve regurgitation, and heart failure underwent redo sternotomy, which resulted in an intraoperative right ventricle injury. She required extracorporeal membrane oxygenation support because of low blood pressure and subsequently developed complications, including surgical site hematoma, wound dehiscence, and fat necrosis. She was referred for wound closure, where a significant 10×20-cm soft tissue defect in the anterior chest wall was observed. A pedicled vertical rectus abdominis myocutaneous flap addressed the soft tissue defect. The wound showed remarkable improvement at the 8-month follow-up visit. CONCLUSIONS: DSWI management is a complex and multifaceted challenge. NPWT, when combined with appropriate surgical strategies, including wound debridement and flap selection, may promote successful wound healing. This case report highlights the successful management of a complex DSWI using a multidisciplinary approach, including debridement, appropriate antibiotic therapy, and free-flap reconstruction, which resulted in favorable outcomes.